2013
DOI: 10.1016/j.jml.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Compensation for complete assimilation in speech perception: The case of Korean labial-to-velar assimilation

Abstract: In connected speech, phonological assimilation to neighboring words can lead to pronunciation variants (e.g., 'garden bench'→ "gardem bench"). A large body of literature suggests that listeners use the phonetic context to reconstruct the intended word for assimilation types that often lead to incomplete assimilations (e.g., a pronunciation of "garden" that carries cues for both a labial [m] and an alveolar [n]). In the current paper, we show that a similar context effect is observed for an assimilation that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The first factor is how similar the alternation is to other native language phonological processes. Several studies have shown that a listener's native language phonology influences lexical processing (Darcy et al, 2007;Darcy et al, 2009;Mitterer et al, 2013;Pallier et al, 2001; but c.f. Gow & Im, 2004;Mitterer et al, 2006).…”
Section: Unanswered Questions and The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The first factor is how similar the alternation is to other native language phonological processes. Several studies have shown that a listener's native language phonology influences lexical processing (Darcy et al, 2007;Darcy et al, 2009;Mitterer et al, 2013;Pallier et al, 2001; but c.f. Gow & Im, 2004;Mitterer et al, 2006).…”
Section: Unanswered Questions and The Current Studymentioning
confidence: 99%
“…In contrast, phonological inference models (Darcy et al, 2009;Gaskell & Marslen-Wilson, 1996Lee & Pater, 2008;Mitterer et al, 2013) also posit abstract representations, but argue that listeners use phonological context to recover an abstract surface form, working backward from the phonetic form. For instance, upon hearing an assimilated form like leam bacon, the listener recognizes that the [b] in bacon may license assimilation of a preceding coronal nasal, and so the listener can identify the intended lean.…”
Section: Introductionmentioning
confidence: 99%
“…All languages have phonological rules that change the canonical sound shape of words when they are pronounced within sentences. During spoken language processing, listeners automatically 'undo' the changes they bring about in order to retrieve the canonical word form [1][2][3][4][5][6][7][8][9]. Most research on this so-called compensation has focused on assimilation rules, such as English place assimilation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, listeners compensate for the phonological change in a context-sensitive manner. Furthermore, they do so not only when traces of the underlying phoneme are present in the assimilated word, but also -although often to a lesser extent -when assimilation is complete or nearly complete [2,[5][6][7][8][9] (but cf. [4]).…”
Section: Introductionmentioning
confidence: 99%
“…Taking the Korean labial-to-velar assimilation rule as a hypothetical example, the surface velarvelar can underlyingly be either a labial-velar sequence, in which the underlying labial is neutralized to a surface velar, or a true velar-velar sequence. Native listeners have been amply demonstrated to be able to undo the neutralization and map the surface element onto the non-surface-matching underlying element, based on language-specific phonological knowledge about the underlying-to-surface (henceforth, U-to-S) process and lexical underlying representations [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%